Exploration of the mechanism underlying the impact of artificial light on guinea pig ovarian function via proteomics and acetylation analyses - Jiayu Shi; Yuliang Wang; Linfang Li; Ruxin Wang; Yao Peng; Tingting Zhou; Donglai Hu; Jie Chen; Yong Tan (Ecotoxicology and Environmental Safety)
Objective: This study aims to explore the effects of artificial light on ovarian function in female guinea pigs and the possible mechanism. Methods: The levels of serum sex hormone expression in the natural light group (N) and LED group (L) were detected via ELISA. The differentially expressed proteins and changes to acetylation levels in the ovaries of female guinea pigs from both groups were analysed via 4D-DIA proteomics and 4D-DIA acetylation quantitative proteomics. The potential mechanisms by which artificial light causes ovarian dysfunction in female guinea pigs were identified, and the results of proteomics and acetylation modification studies were validated via WB and IHC. Results: The androgen, oestrogen, dehydroepiandrosterone sulphate, and luteinizing hormone levels in guinea pig serum, were lower in the LED group than in the natural light group. Follicle-stimulating hormone and sex hormone-binding globulin exhibit the opposite trend. Proteomics showed the decrease of protein expression levels of StAR, which was verified by WB and IHC. Quantitative proteomics for acetylation revealed that Bmal1 underwent acetylation at 111 sites. The level of Bmal1 acetylation in guinea pig ovaries was verified via WB, which revealed an increasing trend. WB and IHC revealed an increase in the protein levels of TIP60 and Cry1. Conclusion: Artificial light affects ovarian dysfunction in female guinea pigs may involve the acetylation at site 111 of Bmal1. This affects Cry1 accumulation, inhibits the transcriptional activity of the circadian gene loop, influences StAR formation, and consequently impacts their ovarian function.